Population and Landscape Genetics Provide Insights Into Species Conservation of Two Evergreen Oaks in Qinghai–Tibet Plateau and Adjacent Regions - Liu, Keke; Qi, Min; Du, Fang K. (Frontiers in Plant Science, 2022)
The combination of population and landscape genetics can facilitate the understanding of conservation strategy under the changing climatic. Here, we focused on two most diverse and ecologically important evergreen oaks: Quercus aquifolioides and Quercus spinosa in Qinghai-Tibetan Plateau (QTP), which is considered as world's biodiversity hotspot. We genotyped 1 657 individuals of 106 populations at 15 nuclear microsatellite loci throughout the species distribution range. Spatial patterns of genetic diversity were identified by mapping the allelic richness (AR) and locally common alleles (LCA) according to the circular neighborhood methodology. Migration routes from QTP were detected by approximate Bayesian computation and historical gene flow estimation. The response pattern of genetic variation to environmental gradient was assessed by the genotype-environment associations (GEAs) analysis. The overall genetic structure showed a high level of intra-species genetic divergence of strong west-east pattern. The West-to-East migration route indicted the complex demographic history of two oak species. We found evidences of isolation by environment in Q. aqu-East and Q. spi-West lineage but not in Q. aqu-West and Q. spi-East lineage. Furthermore, populations with higher spatial genetic diversity and isolated at the edge of the distribution range both should be considered in conservation activities. Our findings indicate that knowledge of spatial diversity and migration route can provide valuable information for the conservation of existing populations. This study provides an important guide for species conservation for two oak species by integration of population and landscape genetic methods.